2020
DOI: 10.1167/tvst.9.5.8
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Macular Inner Retinal Layer Thickness Asymmetry Evaluated by Optical Coherence Tomography to Detect Preperimetric Glaucoma

Abstract: Citation: Takemoto D, Higashide T, Ohkubo S, Udagawa S, Sugiyama K. Ability of macular inner retinal layer thickness asymmetry evaluated by optical coherence tomography to detect preperimetric glaucoma. Trans Vis Sci Tech. 2020;9(5):8, https://doi.org/10.1167/tvst.9.5.8 Purpose:We assessed the ability to detect preperimetric glaucoma (PPG) based on asymmetry in the thickness of the macular inner retinal layers measured by spectraldomain optical coherence tomography. Methods:We studied 45 normal eyes and 50 PPG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Due to the inter-eye and inter-individual variations, several authors investigated a role of intraocular macular thickness asymmetry between superior and inferior retinal hemispheres, as a structural biometric for detecting pathological conditions. Various methods of estimation including an absolute mean difference, an inferior to superior retinal thickness ratio, and asymmetric index (a logarithmic ratio of inferior/superior retinal thickness) have confirmed a discriminative ability of intraocular thickness asymmetry to define pathologies [29‒38]. In a report using the Spectralis posterior pole retinal thickness scan protocol, Sullivan-Mee et al [29] found that a global absolute mean intraocular macular thickness asymmetry was one of the robust OCT diagnostic parameters for differentiating healthy and early glaucoma subjects, with 77% sensitivity and 80% specificity using a 9-µm cut-off point.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the inter-eye and inter-individual variations, several authors investigated a role of intraocular macular thickness asymmetry between superior and inferior retinal hemispheres, as a structural biometric for detecting pathological conditions. Various methods of estimation including an absolute mean difference, an inferior to superior retinal thickness ratio, and asymmetric index (a logarithmic ratio of inferior/superior retinal thickness) have confirmed a discriminative ability of intraocular thickness asymmetry to define pathologies [29‒38]. In a report using the Spectralis posterior pole retinal thickness scan protocol, Sullivan-Mee et al [29] found that a global absolute mean intraocular macular thickness asymmetry was one of the robust OCT diagnostic parameters for differentiating healthy and early glaucoma subjects, with 77% sensitivity and 80% specificity using a 9-µm cut-off point.…”
Section: Discussionmentioning
confidence: 99%
“…This logic included (1) the absolute value of each layer thickness of the whole or separate regions, 36 (2) vertical difference in peripapillary RNFL thickness, 35 (3) vertical and lateral difference of each layer in the macular area, 34 (4) wedge-shaped localized retinal NFLD around the optic disc, 37 (5) difference in the double hump pattern of the peripapillary RNFL, 38 (6) absolute value of the low value of the double hump pattern of the peripapillary RNFL, 38 and (7) axial length estimated from the angle of the double hump pattern of the peripapillary RNFL. Furthermore, in the macula, three patterns were examined using (A) whole data (model 1); (B) exclusion of surrounding areas to avoid the influence of large vessels (model 2) 39 ; and (C) exclusion of the central area on the basis that this area is not affected in early stage glaucoma (model 3). On implementation of all three algorithms, the odds ratio of variables regarding the vertical and laterality difference of each layer was the strongest indicator of glaucoma.…”
Section: Discussionmentioning
confidence: 99%